PENGARUH PUBLIKASI SADAR WISATA DI MEDIA RADIO TERHADAP KALANGAN PELAJAR - Usman Chamdani (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2016)
Radio is an efficient medium to spread information about tourism development. This research focus on the tourism awareness information that has been broadcasted and how it influenced the student of SMU Negeri (Public High School) 8 Bekasi. The qualitative method used in the research shows that the broadcast on tourism awareness influenced the student’s awareness and attitude, but not the behavior. This means that the students know and support the message they listened from the radio, though they still did not apply it. The recommendations from the research are creating entertaining and catchy message, adding the broadcast time and airing it regularly, as well as creating interactive dialogue with idolized broadcaster who spread the tourism message which is beneficial for students.